Theory and problems of theoretical mechanics - Spiegel, Murray R; Spiegel, Murray R. (New Delhi, McGraw-Hill, 2006)
The purpose of this book to present Newtonian Mechanics and its application in a lucid and easy to understand style. For this reason it has maintained its fundamental importance in science and engineering. This book is designed for the use either as supplement to all current standards textbooks or as a textbook for a formal course in mechanics.
Appendix A-D 339-360p.; Index 361-368p.; Reprint 2016.
Keywords: Central forces; Lagranges equations; Moving coordinate systems; Physics